The Investment Decision on Generation Z in Pontianak - Ceci Lia Chen; Nina Febriana Dosinta (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2023)
In today's digital age, accessing information that can influence millennials to participate in capital markets has become more accessible. The desire to secure one's future is a motivating factor that drives individuals to act toward investing. This study assesses the effect of financial literacy, financial experience, locus of control, experience regret, and accounting information on investment decisions. Processed data is primary data obtained from distributing questionnaires with a purposive sampling technique to generation Z in Pontianak and analyzed using multiple linear regression analysis techniques. This study used a sample of 103 respondents and the SPSS (Statistical Program for Social Science) program to process the data. The results showed that Gen Z in Pontianak considers locus of control, experience regret, and accounting information to make investment decisions. Financial literacy and financial experience are outside the benchmark for making investment decisions on Gen Z in Pontianak. These findings indicate that most respondents consider the locus of control, experience of regret, and accounting information in making investment decisions. Then, most respondents must focus more intensely on financial literacy and experience to make the right investment decisions. The implications of this research indicate that applying mental accounting and prospects can assist investors in managing finances and making the right investment decisions to maximize profits. Keywords: Accounting Information, Experience Regret, Investment Decisions, Locus of Control Abstrak Di era digital seperti sekarang ini, akses informasi yang dapat mempengaruhi generasi milenial untuk berpartisipasi di pasar modal menjadi lebih mudah. Keinginan untuk mengamankan masa depan merupakan faktor pendorong yang mendorong individu untuk melakukan investasi di pasar modal. Penelitian ini menilai pengaruh literasi keuangan, pengalaman keuangan, locus of control, pengalaman penyesalan, dan informasi akuntansi terhadap keputusan investasi. Data yang diolah merupakan data primer yang diperoleh dari penyebaran kuesioner dengan teknik purposive sampling kepada generasi Z di Pontianak dan dianalisis dengan menggunakan teknik analisis regresi linier berganda. Penelitian ini menggunakan sampel sebanyak 103 responden dan program SPSS (Statistical Program for Social Science) untuk mengolah data. Hasil penelitian menunjukkan bahwa Gen Z di Pontianak memperhatikan locus of control, pengalaman penyesalan, dan informasi akuntansi dalam membuat keputusan investasi. Literasi keuangan dan pengalaman keuangan tidak menjadi tolak ukur dalam pengambilan keputusan investasi pada Gen Z di Pontianak. Temuan ini menunjukkan bahwa mayoritas responden mempertimbangkan locus of control, pengalaman penyesalan, dan informasi akuntansi dalam membuat keputusan investasi. Kemudian, mayoritas responden perlu memfokuskan lebih mendalam tentang literasi keuangan dan pengalaman untuk membuat keputusan investasi yang tepat. Implikasi penelitian ini mengindikasikan bahwa penerapan mental accounting dan prospek dapat membantu investor dalam mengelola keuangan dan pembuatan keputusan investasi yang tepat dalam memaksimalkan keuntungan. Kata kunci: informasi akuntansi, pengalaman penyesalan, keputusan investasi, locus of control